Rachunek kosztów uzyskania przychodów - Poszwa, Michał (Tax cost accounting, 2009)
In Polish law there are different rules of tax depreciation in personal partnerships and capital companies. There is a problem appearing of the different charging of both kinds of tax depreciation methodology in the wide range the rules of competition. Moreover the different tax depreciation methodology causes the necessity of deciding which method is more profitable for the taxpayer. Setting the cost-effectiveness is very difficult and demands using profit calculation. The final decision about the form of business activity is very risky. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu, 2009, Nr 53, s. 101-108